Neurotoksokarijaza: Prikaz bolesnika u korelaciji sa kliničkim simpotomima i radiološkim imidžingom - Todorović, Stefan (Acta medica Medianae, 2021)
Human toxocariasis is a parasitic infection caused by the roundworms Toxocara canis or Toxocara cati. Toxocara larvae can cross the blood-brain barrier leading to the neurotoxocariasis. Involvement of the central nervous system is extremely rare. The clinical presentation consists of a wide spectrum of neurological manifestation. Herein we present a case of a 63–year–old woman with a rapidly progreesive form of neurotoxocariasis. Her initial head computed tomography scan showed multiple hypervascular lesions in her brain and a contrast enhanced magnetic resonance imaging scan showed multiple T1W and T2W enchancing lesions in basal ganglia and cerebellum. Thereafter, in further processing, serological tests showed presence higher titar of anti-Toxocara antibody in the serum, presence of eosinophilia in the serum or cerebrospinal fluid. This case highlights an unsual case of neurotoxocariasis in the nonendemic area, in a patient who was not immunocompromised, who was diagnosed with serological tests and reviews the relevant radiological findings.
Keywords: toksokarijaza; centralni nervni sistem; neurotoksokarijaza